Inflation and hyperinflation countries in 2018-2020: Risks of different assets and foreign trade - Olli-Pekka Hilmola (Journal of Risk and Financial Management, 2021)
Since the global financial crisis (2008-2009), central banks and governments in developed countries have relied upon loose monetary and financial policy. In the coronavirus pandemic era, these policies were taken even more to the extreme. In 2021, countries around the world started to experience product availability issues, and inflation in some cases was extremely high. There has been debate about the possibility of persistent high inflation. However, risks to assets and foreign trade in this new situation are unknown as all important hyperinflation cases are from decades to century-old. It is important to know what kind of implications high inflation has on modern economies. Therefore, in this study, 10 countries with the highest inflation were selected to be examined in the period of 2018-2020. In these countries, currencies lost a considerable amount of their value against US dollar in 2018-2020. Stock market indexes in many cases provided very high returns in local currency terms; however, against the US dollar, the index yield changed for the substantially negative. Apartment prices in general declined as well. In foreign trade, imports generally declined, while exports were mixed or even increased. However, it should be noted that all of these observations are influenced by the pandemic era and special circumstances of a particular country.
Keywords: 330; inflation; hyperinflation; currency; stock market; real estate; import; export